Applications on mobile devices as a new possibility of assistive technology for reading and writing activities - Borges, Wanessa Ferreira; Mendes, Eniceia Gonçalves (Seven Editora, 2023)
In the implementation of conventional Assistive Technology (AT) resources, a challenge is the acceptance and use of these devices by their users. However, technological development brings to the context of people with low vision new possibilities for AT resources, the applications in smartphones and tablets. Given this new reality, the present study aimed to identify and describe applications that take on the role of AT used in reading and writing tasks performed by people with low vision with the aid of mobile devices. The study included 28 people with low vision, who are members of an existing group on the WhatsApp application. Data collection took place in the virtual space of this application, individually, utilizing semi-structured interviews. The data were transcribed and organized into two categories of analysis: applications used and functionality. The participants mentioned 36 applications, which functionally assume the function of electronic magnifiers; digitizers and OCR programs, text readers; object and color identifiers; icon enlargers and keyboard contrast changes; digital bookshelves; and applications that assume an AT function because they are inaccessible devices. The survey revealed the potential of these applications in solving reading and writing difficulties faced by people with low vision, suggesting more research, investments, dissemination, and education programs to increase their use. DOI: https://doi.org/10.56238/devopinterscie-036